Triglyceride-glucose index and estimated 10-year risk of a first hard cardiovascular event - Qu, Hua; Long, Lin-zi; Chen, Li; Wu, Han-tao; Fu, Chang-geng; Zhang, Shan-shan (Frontiers in Cardiovascular Medicine, 2023)
Background: Whether Triglyceride-glucose (TyG) index is associated with 10-year risk of a first hard atherosclerotic cardiovascular disease (ASCVD) event in the United States remains unclear. Methods: In this cross-sectional study, the participants, ranged from 40 to 79 years old, were from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2018. TyG index was the independent variable and 10-year risk of a first hard ASCVD was the dependent variable. The other variables, such as age, gender, race, body mass index (BMI), hypertension treatment states, smoking states and low-density lipoprotein cholesterol (LDL-C) et al. were considered as the potential confounding factors. Multivariate linear regression models and smooth curve fittings were used to evaluate the association between TyG index and 10-year risk of a first hard ASCVD event. Results: A total of 2142 participants were included in the analysis. The results showed that TyG index was associated with an increased 10-year risk of a first hard ASCVD event [β=1.682, 95% (1.246, 2.118), P<0.00001]. The association had statistical significance in both men [β=2.834, 95%CI (2.302, 3.367), P<0.00001] and women [β=1.023, 95%CI (0.335, 1.711), P=0.00365)] according to subgroup analysis. Smooth curve fittings revealed that TyG index was linearly associated with 10-year risk of ASCVD in both male and female. Moreover, TyG index reached a saturation curve in male and the inflection point was identified at 9.812. Conclusions: TyG index was associated with an increased 10-year risk of a first hard ASCVD event in the United States, suggesting it is necessary to monitor and control an appropriate range of TyG index.